Genomic diversity of burkholderia pseudomalleiIsolates, Colombia (2021)
We report an analysis of the genomic diversity of isolates of Burkholderia pseudomallei, the cause of melioidosis, recovered in Colombia from routine surveillance during 2016–2017. B. pseudomallei appears genetically diverse, suggesting it is well established and has spread across the region.